Eksplorasi Hambatan-hambatan Siswa Dalam Memecahkan Masalah Program Linear di Sekolah Menengah Kejuruan - Andono, Joko; Nugroho, Purna Bayu; Handayani, Ratih (International Journal of Progressive Mathematics Education, 2022)
This study aims to identify the difficulties of class X students of SMK Muhammadiyah 1 Kotabumi in studying Mathematics in the Linear Program material. The type and approach in this research is descriptive research with a qualitative approach. The data collection techniques in this study were tests, observations, questionnaires, while for data processing the percentage formula was P = f/n x 100%. From the results of the research, it can be concluded that the difficulties of students in class X SMK Muhammadiyah Kotabumi in Linear Program material are the lack of understanding of students in understanding the concept of Linear Programs, often using formulas incorrectly and still confused in making a mathematical model, as well as the teacher's habit of learning mathematics in a different way. , just take notes on the blackboard, then students lack the desire to complete the sample questions given by the teacher. So it can be concluded that the hypothesis is proven true that there are learning difficulties in mathematics lessons in the Linear Program material for class X SMK Muhammadiyah 1 Kotabumi.